Design and Evaluation of New Unified Criteria for Disseminated Intravascular Coagulation Based on the Japanese Association for Acute Medicine Criteria. (March 2016) - Umemura, Yutaka; Yamakawa, Kazuma; Kiguchi, Takeyuki; Yoshikawa, Yoshiaki; Ogura, Hiroshi; Shimazu, Takeshi; Hamasaki, Toshimitsu; Fujimi, Satoshi
Background: Current disseminated intravascular coagulation (DIC) criteria are insufficient for predicting mortality. Hemostatic endothelial molecular markers are useful for DIC diagnoses. We aimed to design new DIC criteria involving these markers based on the recently published Japanese Association for Acute Medicine (JAAM) DIC criteria, which exhibit higher sensitivity for mortality. Materials and Methods: Patients with severe sepsis or septic shock admitted to a tertiary referral hospital in Japan between September 2009 and November 2011 were included. Clinical data, including hemostatic endothelial molecular markers, were measured within 12 hours after admission. Receiver operating characteristic analyses were conducted for 8 candidate variables to identify the mortality-related markers. Then, we designed new unified criteria based on the JAAM DIC criteria and involving the identified optimal markers. Results: Of the 79 patients, 66 (83.5%) survived and 13 (16.5%) died. Protein C activity correlated best with mortality with a very high prognostic value (area under the curves [AUCs] = 0.850; P < .001), followed by plasminogen activator inhibitor 1 (AUC = 0.828; P < .001). The unified criteria, consisting of the JAAM DIC criteria plus these 2 markers, exhibited greater prognostic value for mortality (sensitivity, 84.6%; specificity, 80.3%). Moreover, DIC-positive patients using the unified criteria had significantly higher disease severity, as indicated by the Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment scores. Conclusion: Our unified criteria involving hemostatic endothelial molecular markers reflected not only mortality but also the severity of illness in patients with severe sepsis.